Pequena angular; Almada em relance : notas-relâmpago acerca da obra literária de José de Almada Negreiros no centenário de Orpheu - Silva, Celina (2015)
Reading of the literary work of Almada Negreiros concerning its constantly changing procedures, and focusing the major examples of its writing in order to underline the fundamental unity of its creative nucleus which lies in an experimental practice. This authors writings show the main literary practice created around Orpheu (1915), portuguese vanguard movement, by activating the linguistic and literary codes in order to renew the paradigms. Later Almadas work adopts a quite different record on which modernity and tradition dialogue in a critical and original way. This particular attitude and style was called by Almada Naivety.